Adolescent Hepatitis C: Prevalence, Impact, and Management Challenges - Mari PC; Gulati R; Fragassi P (Dove Medical Press, 2021)
Paula Chaves Mari, Reema Gulati, Philip Fragassi Department of Pediatrics, MetroHealth Medical Center, Cleveland, OH, USACorrespondence: Philip FragassiMetroHealth Medical Center, 2500 MetroHealth Drive, Cleveland, OH, 44109, USATel +1 216 957 5000Fax +1 216 252 1118Email pfragassi@metrohealth.orgAbstract: The prevalence of Hepatitis C virus infection (HCV), a leading cause of chronic liver disease worldwide, is rising in the United States (US) and other high-income countries, especially among youth and young adults. This surge in cases is closely associated with the opioid crisis and intravenous drug use (IVDU). However, its prevalence and impact on the adolescent population have not been thoroughly studied and therefore is poorly understood. The pediatric population tends to have milder liver disease and progression when compared to adults; however, there is a risk of developing liver cirrhosis, in addition to facing decreased quality of life and stigmatization from the disease. The recent approval of direct-acting antiviral (DAA) regimens for all HCV genotypes and age greater than 3 years has revolutionized its management. Therapy has shifted from the prolonged interferon-based regimens, to shorter duration, once daily oral pills that are highly effective, curative and with fewer side effects. Therapy is now indicated for all adolescents with hepatitis C virus infection, regardless of stage of liver disease, recent IVDU, or coinfection with HIV, therefore eliminating a lifetime risk of chronic liver disease, cirrhosis and hepatocarcinoma. Nonetheless, adolescents are rarely tested or treated for hepatitis C infection, and very few adolescents complete therapy. Implementation of point of care (POC) testing of high-risk youth at drug treatment centers or other juvenile facilities may be a good strategy to increase testing, diagnosis and therapy. This review article aims to educate pediatricians and other primary care providers to help decrease the existing knowledge gap on the subject.Keywords: HCV, pediatric, IVDU, DAA, opiate